Digital Marketing Adoption And Its Impact On Business Sustainability Of MSMEs In West Sumatra - Sutiyem Sutiyem; Desy Trismiyanti; Yulina Eliza; Yass Andria; Irwan Muslim (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
The rapid advancement of digital technology has encouraged Micro, Small, and Medium Enterprises (MSMEs) to adopt digital marketing as a strategic approach to sustaining business performance. This study aims to examine the effect of digital marketing adoption on business sustainability among MSMEs in West Sumatra. Digital marketing adoption is operationalized through social media usage, e-commerce platform utilization, digital content quality, and digital marketing analytics usage. This research employs a quantitative approach using a survey method targeting MSMEs that have implemented digital marketing practices. Data were analyzed using multiple linear regression with the support of IBM SPSS version 25. The findings reveal that e-commerce platform utilization, digital content quality, and digital marketing analytics usage have a positive and significant impact on business sustainability, whereas social media marketing usage does not exhibit a significant effect. These results indicate that effective utilization of e-commerce platforms plays the most dominant role in enhancing business sustainability, followed by the quality of digital content and the application of marketing analytics. The negative and significant constant suggests the presence of other influential factors beyond the proposed research model. From a policy perspective, the study highlights the need to prioritize strengthening e-commerce utilization, alongside improving digital content development and analytics capabilities through integrated and sustainable MSME capacity-building programs. Furthermore, this study recommends enhancing MSMEs’ digital literacy through continuous training and mentoring, while encouraging future research to incorporate additional variables and employ more comprehensive analytical methods.